Electronic contracts on medical care of the population under medical guarantees program - V. A. Кroitor (Bulletin of Kharkiv National University of Internal Affairs)
On the basis of the conducted research, the author has proved that the specific feature of electronic contracts on medical care of the population under medical guarantees program is that: it is exclusively signed through the electronic health care system, is considered an electronic document, must meet all the requirements established for a civil contract. The author has identified the principles of electronic medical deeds: information exchange takes place exclusively in electronic form; the legislation establishes the security of exchange and preservation of medical information, in particular medical confidentiality; modern access to medical care and resources is provided due to their assistance; these electronic contracts are aimed at improving the quality of service and meeting patients needs, transparency of the health care system; they are signed considering technological neutrality and independence from decisions developers; while signing such contracts, the information is recorded in the e-health system without the possibility of deleting or correcting the entered data; electronic identification and authentication of participants in medical relations with a high level of trust is used while they are being signed. It has been established that signing a contract on medical care of the population under medical guarantees program includes the following stages: 1) the National Health Service of Ukraine publishes an announcement on the official website about the intention to sign such a contract under certain conditions; 2) a business entity that wishes to sign a contract with the National Health Service of Ukraine on the terms specified in the announcement must ensure that up-to-date information about its business activity, the possibility of medical practice, is entered into the system before submitting a proposal; 3) the National Health Service of Ukraine considers the received proposals within the definite term; 4) signing a draft contract by an authorized person of the National Health Service of Ukraine, which is a proposal to sign a contract (offer) with a validity period of ten calendar days from the date of its signing by an authorized person of the National Health Service of Ukraine.